2007
DOI: 10.1152/ajpheart.00436.2007
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent coronary metabolic dilation

Abstract: We have observed that hydrogen peroxide (H 2O2), the dismutated product of superoxide, is a coronary metabolic dilator and couples myocardial oxygen consumption to coronary blood flow. Because the chemical activity of H 2O2 favors its role as an oxidant, and thiol groups are susceptible to oxidation, we hypothesized that coronary metabolic dilation occurs via a redox mechanism involving thiol oxidation. To test this hypothesis, we studied the mechanisms of dilation of isolated coronary arterioles to metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 23 publications
2
57
0
Order By: Relevance
“…Our current data support the concept that abnormal endothelium-dependent vasodilatation is mediated by superoxide rather than H 2 O 2 as it was ameliorated by anti-PECAM/SOD and not by anti-PECAM/catalase delivery, despite the fact that the latter increased local degradation of H 2 O 2 . This negative outcome agrees with reports that H 2 O 2 functions as a vasodilator rather than as a vasoconstrictor in some types of vessels (Cai, 2005;Saitoh et al, 2007). In contrast, accumulation of SOD in endothelium, achieved by anti-PECAM/SOD, but not the unconjugated counterpart, quenched superoxide and protected BH 4 (and, presumably, NO), thus enhancing endothelium-dependent vasodilatation.…”
Section: Ros Detoxification In Endotheliumsupporting
confidence: 90%
“…Our current data support the concept that abnormal endothelium-dependent vasodilatation is mediated by superoxide rather than H 2 O 2 as it was ameliorated by anti-PECAM/SOD and not by anti-PECAM/catalase delivery, despite the fact that the latter increased local degradation of H 2 O 2 . This negative outcome agrees with reports that H 2 O 2 functions as a vasodilator rather than as a vasoconstrictor in some types of vessels (Cai, 2005;Saitoh et al, 2007). In contrast, accumulation of SOD in endothelium, achieved by anti-PECAM/SOD, but not the unconjugated counterpart, quenched superoxide and protected BH 4 (and, presumably, NO), thus enhancing endothelium-dependent vasodilatation.…”
Section: Ros Detoxification In Endotheliumsupporting
confidence: 90%
“…Numerous studies have shown that, under a variety of stressed conditions, Nox2 or mitochondria-derived radicals impair endothelial function via reductions in nitric oxide bioavailability (7,14,15,40). Conversely, several studies have reported that mitochondria-derived H 2 O 2 elicits vasodilation in coronary arteries (24,35,36,42) and that Nox4-derived ROS may play a central role in maintaining nitric oxide bioavailability (37). Interestingly, incubation of vessels from MnSOD ϩ/ϩ with catalase improved relaxation to acetylcholine, an effect that is likely due to increased NO bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…It is now clear that normal levels of cellular ROS and RNS play important roles in cell-signaling pathways and are vital for physiological functions. For instance, H 2 O 2 of mitochondrial origin are of paramount importance in metabolic coronary vasodilatation (307).…”
Section: Ros and Rns Such As Omentioning
confidence: 99%
“…Indeed, even under physiological conditions, a minor fraction of oxygen ( < 0.1%) is transformed into O 2 -at the level of complexes I and III; SOD then rapidly converts O 2 -to H 2 O 2 that is freely diffusible through membranes (110). The production of H 2 O 2 can increase during myocardial challenging, such as during increased cardiac work load (307 or Cu 2 + , represents a dangerous step, because an increase in toxicity can occur. In fact, no enzyme is available for the removal of OH that can only be scavenged by antioxidants with the formation of less-dangerous radical species.…”
Section: Ros and Rns Such As Omentioning
confidence: 99%